Eksistensi dan Relevansi Pembelajaran Ilmu Tafsir terhadap Pemahaman Keagamaan Peserta Didik - Nadiya Ulya Rahmatika; Wajidi Sayadi; Muhammad Tisna Nugraha (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the existence of tafsir learning at MAN 1 Pontianak and assess its relevance to students' religious understanding. The focus of the study includes the form, process, and continuity of tafsir learning, as well as its impact on students' appreciation of social and religious values in their daily lives. This study uses a descriptive qualitative approach, with data collection methods through participatory observation, in-depth interviews, and analysis of documents related to the curriculum and practices of tafsir learning. The data are analyzed thematically to describe the learning phenomenon and its relevance in detail. The results show that the teaching of tafsir at MAN 1 Pontianak not only emphasizes academic understanding of the Qur'anic text but also shapes students' religious awareness and behavior. The systematic, interactive, and contextual learning process successfully improved students' cognitive understanding, affective attitudes, and psychomotor skills in applying religious values in social life. Thus, tafsir learning proved to be relevant in supporting the character building and religious life of students, while strengthening social relationships based on Islamic values